Study of obstructive jaundice in adult: association between clinical diagnosis and operative "ndings (Bangladesh Medical Journal, 2019)
Obstructive jaundice is a condition in which there is blockage of the flow of bile out of the liver. To find out the correlation between clinical diagnosis and operative findings of patients having obstructive jaundice. This prospective observational study was conducted at the Department of Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2008 to April 2009. Fifty clinically diagnosed obstructive jaundice cases were enrolled in this study. A detailed history was taken and thorough physical examination was done. Also necessary haematological, biochemical, radiological and other special investigations were carried out.  In this study, mean age of the patients was 42.9 years and male to female ratio was 1:1.17. The most frequent cause was choledocholithiasis (40%), stricture of CBD (6.0%), retained stone (14.0%), parasitic obstruction (4.0%), carcinoma (30.0%) and other cause (6.0%). Serum bilirubin level was below 10mg/dl in all cases of stricture of CBD. It was above 15mg/dL in cases of carcinoma head of the pancreas. The rise of Serum alkaline phosphates level was up to 3 folds in cases with choledocholithiasis, biliary stricture and pancreatic head malignancy. The average rise in other cases was 1 to 2 folds. Sensitivity and specificity of pre operative clinical diagnosis of choledocholithiasis, carcinoma and retain stone was 86.4 & 96.4%, 92.3 & 91.9% and 71.4 & 95.3% respectively. Pre operative clinical diagnosis of obstructive jaundice is a good diagnosis tool in diagnosis of causes of obstructive jaundice.Bangladesh Med J. 2018 Jan; 47 (1): 33-36